The relationship of KDIGO classification and incidence & mortality of acute kidney injury in sepsis patients in intensive care unit: A retrospective cohort study: Acute kidney injury in sepsis patients in ICU - Mecit, Bilge Banu Taşdemir; Deniz, Mustafa (Journal of Surgery and Medicine, 2023)
Background/Aim: Acute kidney injury (AKI) is a common and serious complication associated with morbidity and mortality in patients with sepsis. This study aimed to determine the severity of AKI according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria and evaluate its relationship with mortality in patients who were followed up in the intensive care unit (ICU) due to sepsis and developed AKI. Methods: We retrospectively analyzed patients diagnosed with sepsis and followed up in the ICU, including all patients with AKI. The severity of AKI was determined for all patients using the KDIGO criteria. The patients were divided into four groups: Stage 1, Stage 2, Stage 3, and without AKI. Patients with missing data, COVID-19 patients, patients with chronic kidney insufficiency, and kidney transplant patients were excluded. Results: A total of 1,177 sepsis patients were included in the study, of whom 52.4% were male (n=617). The median age of the study group was 78 years (Q1-Q3: 68-85 years). It was determined that 57.9% of the patients (n=681) developed AKI at any stage. According to the KDIGO criteria, the rates of patients in Stage 1, Stage 2, and Stage 3 developing AKI were 23.9%, 16.2%, and 17.8%, respectively. The incidence of hypertension (HT) and diabetes mellitus (DM), which are comorbidities, increased as the patients’ KDIGO stage increased (P<0.001). Conclusion: AKI occurred in 57.9% of sepsis patients in the ICU, and 30.4% received renal replacement therapy (RRT). It was determined that mortality increased as the KDIGO stage of our patients increased.